E0709 Speckle tracking based circumferential strain analysis to evaluate mechanical function of heart during ventricular pacing: an experimental study on open chest instrumented pigs. (17th November 2010) - Zhiwen, Zhou; Yawei, Xu; Hui, Sun; Weijing, Liu; Xuejing, Yu; David, Sahn
Abstract : Aims: This study aims at assessing ventricular pacing (VP) mechanical change by using global circumferential strain and segmental circumferential strain of speckle tracking imaging. Methods: Seven adult pigs, weighting 30.8±3.6 kg, were sedated, followed by median sternotomy and opening of the pericardium. Temporary pacing leads were placed on the right ventricular epicardium and LV epicardium. A LV short axis view at the mid-level LV was acquired at sinus and VP rhythm. Analysis of circumferential strain based on tracking of acoustic markers was performed offline. The onset of QRS wave was used to characterise the beginning of the cardiac cycle. The ratio of beginning systolic time to cardiac cycle, end systolic time to cardiac cycle and total systolic time to cardiac cycle was calculated for global circumferential strain. We compared those data and dyssynchrony between sinus and VP rhythm. Results: All pigs were successful for VP studying and 84 good images were analysed. Compared with sinus rhythm, in VP rhythm all of the ratio of the beginning systolic time, end systolic time and total systolic time to cardiac cycle were increased (all p<0.05). and the construction of six segments were dyssynchrony, even segmental paradoxical movement. When VP rates were more than 130 bpm, both LV global and LV segments sometimes showed irregular motion while the EKG remained normal pacing EKG, which included: (1) multiple construction and diastole in one heart cycle; (2) A large variability of construction amplitude in several consecutive cardiac cycles. Conclusion: Global and segmental measures of circumferential strain can identify LV mechanical abnormalities induced by VP. VP can lead to several kinds of ventricular mechanical dyssynchrony, including delay and lengthening of LV systole, and irregularity of systole and diastole.